O estresse ocupacional nos trabalhadores (as) de uma unidade de pronto atendimento de Mossoró - Nunes, Paula Caroline Rodrigues (Universidade Federal Rural do Semi-Árido, 2019)
The presence of occupational stress in the daily life of health workers was analyzed in this study as a contribution to the studies in the area of health management. For that, an empirical research was conducted with a qualitative approach, the data collection was carried out through semi-structured interviews and, through the analysis of 10 interviews performed with health professionals of a Emergency Care Unit (UPA) in the city of Mossoró, we were able to organize the results into three broad categories: Stressors, Occupational Stress and Work Senses. Synthetically the results indicate that the workers give meaning to their work in a dichotomous way, oscillating between pleasure and suffering; that they present manifestations of stress given the load of physical and mental effort that their work demands; and that the main stressors are organized around the management of UPA, working conditions, interpersonal relationships and relationship with the external environment. They also report discomfort arising from poor professional recognition, the difficulties of maintaining a balance between work and family and social life, and the impacts of the political and economic situation on the health system and, consequently, on the workplace and on them themselves.
Monografia
Keywords: Estresse ocupacional; UPA; Cotidiano; Trabalhadores da saúde; Occupational stress; UPA; Daily life; Health workers; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO